A Sociological Theory of Postmodernity - Bauman, Zygmunt (Sociologija. Mintis ir veiksmas, 1998)
Translation: Bauman, Zygmunt. 1992. "A Sociological Theory of Postmodernity". In: Intimations of Postmodernity. London and New York: Routledge; 187-204.